Identification of antimalarial leads with dual falcipain-2 and falcipain-3 inhibitory activity - Rana, Devika; Kalamuddin, Md; Sundriyal, Sandeep; Jaiswal, Varun; Sharma, Gaurav; Das Sarma, Koushik; Sijwali, Puran Singh; Mohmmed, Asif; Malhotra, Pawan; Mahindroo, Neeraj (Bioorganic & medicinal chemistry, 2020)
[Display omitted] Falcipains (FPs), cysteine proteases in the malarial parasite, are emerging as the promising antimalarial drug targets. In order to identify novel FP inhibitors, we generated a pharmacophore derived from the reported co-crystal structures of inhibitors of Plasmodium falciparum Falcipain-3 to screen the ZINC library. Further, the filters were applied for dock score, drug-like characters, and clustering of similar structures. Sixteen molecules were purchased and subject to in vitro enzyme (FP-2 and FP-3) inhibition assays. Two compounds showed in vitro inhibition of FP-2 and FP-3 at low µM concentration. The selectivity of the inhibitors can be explained based on the predicted interactions of the molecule in the active site. Further, the inhibitors were evaluated in a functional assay and were found to induce morphological changes in line with their mode of action arresting Plasmodium development. Compound 15 was most potent inhibitor identified in this study.